2013
DOI: 10.1111/jsbm.12000
|View full text |Cite
|
Sign up to set email alerts
|

How On-the-Job Embeddedness Influences New Venture Creation and Growth

Abstract: This study aims to answer why some employees choose to start their own ventures, whereas others choose to seek jobs in other organizations after leaving their current employment. Drawing insights from knowledge‐based view and social capital theory, we examine the impact of on‐the‐job embeddedness on the decision of employee entrepreneurship, industry choice, and new venture growth. We argue that on‐the‐job embeddedness provides key resources for employees to start new ventures and grow them. We test our hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 99 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…We suggest that serial entrepreneurs, were not as reliant on support to enhance their entrepreneurial confidence as they had acquired previous entrepreneurial experience (e.g., Cases 14, 15, and 21) (Mai and Zheng 2013). While the learning experience for novice entrepreneurs usually starts with the self-reflection of being an entrepreneur, serial entrepreneurs already went through the entrepreneurial identification process and thus need less support to reflect on their ability to run a business (see e.g., Kutzhanova, Lyons, and Lichtenstein 2009;Lichtenstein and Lyons 2010).…”
Section: Managing Discrimination Of Older Entrepreneursmentioning
confidence: 79%
“…We suggest that serial entrepreneurs, were not as reliant on support to enhance their entrepreneurial confidence as they had acquired previous entrepreneurial experience (e.g., Cases 14, 15, and 21) (Mai and Zheng 2013). While the learning experience for novice entrepreneurs usually starts with the self-reflection of being an entrepreneur, serial entrepreneurs already went through the entrepreneurial identification process and thus need less support to reflect on their ability to run a business (see e.g., Kutzhanova, Lyons, and Lichtenstein 2009;Lichtenstein and Lyons 2010).…”
Section: Managing Discrimination Of Older Entrepreneursmentioning
confidence: 79%
“…Although some researchers have expressed concern that low turnover rates inhibit employee creativity and innovation related outcomes [26] [27], recent empirical studies indicate that job embeddedness significantly increases innovation [15]. [28] argued that highly embedded employees might be more motivated to engage in innovation because creativity is often a key criterion of pay raises and promotions. [15] empirically suggested that on-the-job embeddedness has a positive influence on employees' innovation-related behaviours.…”
Section: Job Embeddedness and Innovative Work Behaviourmentioning
confidence: 99%
“…Employees who are linked with the various aspects of their lives in the community will get to know their customers' needs through communication with their neighbor. Therefore, the higher number of links between an employee and his/her community network, the higher chance to she or he has to obtain knowledge of customer needs, which will lead to an innovative service delivery process or customized service [28].…”
Section: Job Embeddedness and Innovative Work Behaviourmentioning
confidence: 99%
“…Crossley et al (2007) found that both global JE and composite JE predicted voluntary turnover beyond job attitudes and core variables from traditional models of turnover. Mai et al (2009) analyzed the impact of the embeddedness factors of previous high-tech jobs on the formation of entrepreneurial motivation and the reorganization and development of entrepreneurial opportunities. Result suggests JE influences the probability of employees becoming an entrepreneur.…”
Section: Je and Outcome Variables 411mentioning
confidence: 99%